Radical Ways To Think About Radicalism In Cak Nun's Poets - Mulyono Mulyono; Dhoni Zustiyantoro; Sheyra Silvia Siregar (Universitas Negeri Semarang, 2021)
There is a close relationship between literature and philosophy. Both lead to an appreciation of life with the complexity of the problems that surround it. In her creative work, philosophical thought in literature is interesting to study. The freedom of expression upheld in literature provides free space for the growth and development of an intelligent way of thinking, namely a radical, primary, and necessary form of thinking. This revolutionary way of thinking is needed precisely to tackle radicalism. Research on powerful ways of thought in the poems of Cak Nun (Emha Ainun Nadjib) reminds the poet's existence as a humanist who is familiar with the resolution of social conflicts, including the phenomenon of radicalism. The dialectical hermeneutic approach is used to analyze the philosophical thoughts in these poems. The analysis results show that the roots of radicalism are injustice, arbitrariness, poverty, greed, arrogance, and the use of religion for economic, political, and image purposes.